2017
DOI: 10.1039/c7ay00341b
|View full text |Cite
|
Sign up to set email alerts
|

Detection of small, highly structured RNAs using molecular beacons

Abstract: Efficient detection of small, highly structured RNA (e.g. tRNA) was achieved by selecting the best target region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…We previously showed that the fluorescence intensity of conventional MB in the presence of tRNA Lys3 transcript (15-min reaction) was lower than that of ISMBe and ISMBi in the presence of tRNA transcript (2-h reaction) (Figs 1B and S2B) [18]. These observations suggested that the formation of the ISMBe/tRNA transcript complex requires a relatively long time.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…We previously showed that the fluorescence intensity of conventional MB in the presence of tRNA Lys3 transcript (15-min reaction) was lower than that of ISMBe and ISMBi in the presence of tRNA transcript (2-h reaction) (Figs 1B and S2B) [18]. These observations suggested that the formation of the ISMBe/tRNA transcript complex requires a relatively long time.…”
Section: Resultsmentioning
confidence: 80%
“…The predicted free energies were the same, indicating lack of correlation between the sensitivity of ISMB and the stability of the ISMBe/eMet transcript complex. In a previous study, we showed that conventional MB molecules targeted to the D arm more sensitively detect tRNA Lys3 transcript than those targeted to the anticodon arm and the T arm [18]. Furthermore, according to thermal unfolding studies, the D arm is more readily melted than other regions [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the inherent ability of RNA molecules to fold into complex three-dimensional shapes because of base-pair interactions makes interrogation of natural RNA challenging and limits molecular analysis to the easily accessible loop and bulge RNA regions (Herschlag et al 2018). Indeed, scrupulous and costly analysis of the target accessibility is generally required to select an optimal design of a conventional hybridization probe (e.g., molecular beacon probe [MBP]) (Rhee et al 2008;Li et al 2017). The intrinsic stem in the MBP structure stabilizes the probe, thus disfavoring its interactions with a stem-loop folded targeted fragment to form a probe-target complex (Fig.…”
Section: Introductionmentioning
confidence: 99%